Nd:LYAG and Nd:LGAG Mixed Crystals: Potential Candidates for 1.83 μm Laser Source - Jinglong Lan; Zhi Lin; Yi Wang; Qin Cui; Bin Xu; Huiying Xu; Zhiping Cai; Xiaodong Xu; Jian Zhang; Jun Xu; Richard Moncorge (IEEE Photonics Journal, 2016)
We report here, for the first time, diode-pumped continuous-wave laser operation of Nd:LuYAG (LYAG) and Nd:LuGdAG (LGAG) mixed crystals around 1.83 μm. Cooling the laser samples down to about 6 °C, output powers of about 0.56 and 0.46 W with slope efficiencies of about 5.5% and 5.6% can be achieved, respectively, for the two crystals. These ${\rm{Nd}}^{3+ }{- \rm{doped}}$ garnet mixed crystals, like single crystal Nd:YAG, are believed to be the potential for laser generation at the important 1.83-μm near-infrared wavelength domain.